Protocol to assess rewarding brain stimulation as a learning and memory modulating treatment: Comparison between self-administration and experimenter-administration - Vila-Solés, Laia; García-Brito, Soleil; Aldavert-Vera, Laura; Kádár, Elisabet; Huguet, Gemma; Morgado-Bernal, Ignacio; Segura-Torres, Pilar (Frontiers in Behavioral Neuroscience, 2022)
Intracranial electrical self-stimulation (ICSS) is a useful procedure in animal research. This form of administration ensures that areas of the brain reward system (BRS) are being functionally activated, since the animals must perform an operant response to self-administer an electrical stimulus. Rewarding post-training ICSS of the medial forebrain bundle (MFB), the most important system of the BRS, has been shown to consistently improve rats’ acquisition and retention in several learning tasks. In the clinical setting, deep brain stimulation (DBS) of different targets is currently being used to palliate the memory impairment that occurs in some neurodegenerative diseases. However, the stimulation of the MFB has only been used to treat emotional alterations, not memory disorders. Since DBS stimulation treatments in humans are exclusively administered by external sources, studies comparing the efficacy of that form of application to a self-administered stimulation are key to the translationality of ICSS. This protocol compares self-administered (ICSS) and experimenter-administered (EAS) stimulation of the MFB on the spatial Morris Water Maze task (MWM). c-Fos immunohistochemistry procedure was carried out to evaluate neural activation after retention. Results show that the stimulation of the MFB improves the MWM task regardless of the form of administration, although some differences in c-Fos expression were found. Present results suggest that MFB-ICSS is a valid animal model to study the effects of MFB electrical stimulation on memory, which could guide clinical applications of DBS. The present protocol is a useful guide for establishing ICSS behavior in rats, which could be used as a learning and memory-modulating treatment.